Terminal Hydride Species in [FeFe]‐Hydrogenases Are Vibrationally Coupled to the Active Site Environment. (23rd July 2018) - Pham, Cindy C.; Mulder, David W.; Pelmenschikov, Vladimir; King, Paul W.; Ratzloff, Michael W.; Wang, Hongxin; Mishra, Nakul; Alp, Esen E.; Zhao, Jiyong; Hu, Michael Y.; Tamasaku, Kenji; Yoda, Yoshitaka; et al.
Abstract: A combination of nuclear resonance vibrational spectroscopy (NRVS), FTIR spectroscopy, and DFT calculations was used to observe and characterize Fe−H/D bending modes in Cr HydA1 [FeFe]‐hydrogenase Cys‐to‐Ser variant C169S. Mutagenesis of cysteine to serine at position 169 changes the functional group adjacent to the H‐cluster from a ‐SH to ‐OH, thus altering the proton transfer pathway. The catalytic activity of C169S is significantly reduced compared to that of native Cr HydA1, presumably owing to less efficient proton transfer to the H‐cluster. This mutation enabled effective capture of a hydride/deuteride intermediate and facilitated direct detection of the Fe−H/D normal modes. We observed a significant shift to higher frequency in an Fe−H bending mode of the C169S variant, as compared to previous findings with reconstituted native and oxadithiolate (ODT)‐substituted Cr HydA1. On the basis of DFT calculations, we propose that this shift is caused by the stronger interaction of the ‐OH group of C169S with the bridgehead ‐NH‐ moiety of the active site, as compared to that of the ‐SH group of C169 in the native enzyme.